Stratigraphy and paleogeography of the Eocene in the Mosqueiro Low, Sergipe-Alagoas Basin - Rancan, Cristiano Camelo; Rohn, Rosemarie [UNESP]; Souza-Lima, Wagner; Borba, Claudio (FapUNIFESP (SciELO), 2021)
The oldest petroleum discoveries on the Brazilian offshore margin are in Paleogene reservoirs of the Guaricema and Dourado fields in the structural Mosqueiro Low, the Southern Sergipe-Alagoas Basin. Study of well logs and biostratigraphic data of the Eocene Series allowed its subdivision into three stratigraphic intervals representing the Ypresian, Lutetian-Bartonian, and Priabonian stages. The Ypresian depocenter is in the Dourado Trough, whereas the Lutetian-Bartonian and Priabonian depocenters are in the Vaza-Barris Trough, controlled by halokinesis in the first one and basement deformation in the others. The Ypresian interval mainly comprises retrogradational deposits related to the Early Eocene Climate Optimum. The Middle-Eocene Basal Unconformity is the main erosive feature in the Series. The Lutetian-Bartonian and Priabonian depositional systems are progradational. Their deposition is related to basement uplift due to both intense deep-water magmatism and to the Incaica Phase of the Andean Orogeny.
Keywords: Basement deformation; Brazilian offshore; Gravity flows; Halokinesis; Paleogeography